Changes in iron availability in Arabidopsis are rapidly sensed in the leaf vasculature and impaired sensing leads to opposite transcriptional programs in leaves and roots. (19th June 2018) - Khan, Mather A.; Castro‐Guerrero, Norma A.; McInturf, Samuel A.; Nguyen, Nga T.; Dame, Ashley N.; Wang, Jiaojiao; Bindbeutel, Rebecca K.; Joshi, Trupti; Jurisson, Silvia S.; Nusinow, Dmitri A.; Mendoza‐Cozatl, David G.
Abstract: The OLIGOPEPTIDE TRANSPORTER 3 (OPT3) has recently been identified as a component of the systemic network mediating iron (Fe) deficiency responses in Arabidopsis. Reduced expression of OPT3 induces an over accumulation of Fe in roots and leaves, due in part by an elevated expression of the IRON‐REGULATED TRANSPORTER 1. Here we show however, that opt3 leaves display a transcriptional program consistent with an Fe overload, suggesting that Fe excess is properly sensed in opt3 leaves and that the OPT3‐mediated shoot‐to‐root signaling is critical to prevent a systemic Fe overload. We also took advantage of the tissue‐specific localization of OPT3, together with other Fe‐responsive genes, to determine the timing and location of early transcriptional events during Fe limitation and resupply. Our results show that the leaf vasculature responds more rapidly than roots to both Fe deprivation and resupply, suggesting that the leaf vasculature is within the first tissues that sense and respond to changes in Fe availability. Our data highlight the importance of the leaf vasculature in Fe homeostasis by sensing changes in apoplastic levels of Fe coming through the xylem and relaying this information back to roots via the phloem to regulate Fe uptake at the root level. Abstract : Iron (Fe) is an essential micronutrient that can become toxic at high concentrations. Fe uptake is induced under Fe deficiency and repressed when Fe levels are restored to prevent an Fe overload. Here, we show that Fe deficiency is rapidly sensed in the leaf vasculature and impaired sensing in leaves results in a systemic Fe overload while triggering opposite transcriptional programs in roots and leaves.